Twin Reversed Arterial Perfusion (TRAP) Syndrome or acardiac twin: a case report in Madagascar - Rabetsimamanga, Lyn Z. A.; Rabarikoto, Hary F.; Rajaonarivony, Maheriandrianina F. V.; Ravoavy, Setriny M.; Andrianampanalinarivo, Hery R. (International Journal of Research in Medical Sciences, 2018)
TRAP syndrome is a rare complication of monochorionic twin pregnancy. It is characterized by the association of an acardiac twin with a healthy twin. The acardiac twin is a parasite who put the healthy twin at high risk of cardiac failure. We report a case in a 25-year-old Malagasy woman, primigravida, who had a consultation at gestational week 31 for significant dyspnea and a threat of premature delivery. Ultrasound scans discovered an acute polyhydramnios, fetus with anasarca and low cardiac activity, and a para-fetal mass. She gives birth to a male newborn and an acardiac twin without head an upper body. The first twin died short time after birth.